Evaluation of patient perspective on quality of oral health care in Germany – an exploratory study. (12th July 2013) - Goetz, Katja; Szecsenyi, Joachim; Klingenberg, Anja; Brodowski, Marc; Wensing, Michel; Campbell, Stephen M.
<x xml:space="preserve">Abstract</x> Background Patients' evaluation of care presents an essential dimension of the quality of care. The aim of this exploratory study was to determine which factors of EUROPEP‐Dental were associated with overall patients' evaluation of oral health care. Methods Data were collected from 8, 160 patients from 106 dental practices (response rate 77%) who completed the 30‐item EUROPEP‐Dental questionnaire. The possible answers ranged from 1 (poor) to 5 (excellent). The EUROPEP‐Dental questionnaire covers four domains: 'dentist–patient relationship' (11 items), 'accessibility and waiting time' (10 items), 'quality of care' (six items), 'costs of care' (three items). Each domain was aggregated by mean scores of the associated items. Regression analyses were performed in addition to descriptive analyses. Results Over 66% of the patients were overall positive with their dental care. Linear regression analyses were performed with patient satisfaction as the dependent outcome variable. The item 'medical–technical quality of care' showed the highest score (R² = 0.378) of explained variance, while the EUROPEP‐Dental domain 'quality of care' showed the highest score (R²= 0.467) for explained variance regarding overall patient satisfaction. Conclusions The results are important for understanding patients' priorities with regard to oral health care and for identifying possible areas for improvement of quality. The evaluation of patient perspective on quality of oral health care is likely to continue to be an important aspect of oral health‐care evaluation.